The role of self-efficacy in pain intensity, function, psychological factors, health behaviors, and quality of life in people with rheumatoid arthritis: A systematic review - Martinez-Calderon, Javier; Meeus, Mira; Struyf, Filip; Luque-Suarez, Alejandro (Physiotherapy theory and practice, 2020)
Objective: The aim of this study was to systematically review and critically appraise the role of self-efficacy in pain intensity, function, psychological factors, health behaviors, and quality of life in people with rheumatoid arthritis, based on the analyses of longitudinal studies. Methods: An electronic search of PubMed, AMED, CINAHL, PsycINFO, and PubPsych was carried out from inception to July 2017. Study selection was based on longitudinal studies which have explored the role of self-efficacy in rheumatoid arthritis. The Newcastle-Ottawa Scale adapted version was used to evaluate the risk of bias, whereas the Grading of Recommendations Assessment, Development and Evaluation evaluated the quality of the evidence per outcome. Results: A total of 11 articles met the inclusion criteria. Our results suggest an association between higher self-efficacy and greater goal achievement, positive affect, acceptance of illness, problem-solving coping, physical function, physical activity participation, and quality of life. Inversely, there was also an association between higher self-efficacy and lower pain intensity, depressive symptoms, and anxiety. Conclusions: The findings of this systematic review suggest that self-efficacy might have a positive effect on the prognosis of this condition, although further longitudinal studies are needed.